Peran Mahasiswa MSIB Batch 4 Bank Syariah Indonesia KC Surabaya Basuki Rahmat Terhadap Peningkatan Literasi Keuangan Syariah Di Kota Surabaya - Wibowo, Mohammad Rizal Rifans; Andarini, Sonja (Universitas Gajah Putih, Indonesia, 2023)
Indonesia's economy is one of the countries with significant economic strength in the world. However, the literacy rate among its population is still relatively low. The goal of this community service is to help improve the literacy of the Indonesian population by leveraging the role of Internship Students and Certified Independent Study (MSIB) Batch 4 from PT Bank Syariah Indonesia Regional Office VIII Surabaya. There are a total of 8 participants involved in this community service. The program has been running from January to June 2023 and has been monitored by mentors and accompanying staff. This activity runs in parallel with on-site internship activities. The results achieved show that the community has responded positively to Islamic finance and its prospects for helping improve Indonesia's economy.